2020
DOI: 10.3390/cancers12092600
|View full text |Cite
|
Sign up to set email alerts
|

Jagged Ligands Enhance the Pro-Angiogenic Activity of Multiple Myeloma Cells

Abstract: Multiple myeloma (MM) is an incurable plasma cell malignancy arising primarily within the bone marrow (BM). During MM progression, different modifications occur in the tumor cells and BM microenvironment, including the angiogenic shift characterized by the increased capability of endothelial cells to organize a network, migrate and express angiogenic factors, including vascular endothelial growth factor (VEGF). Here, we studied the functional outcome of the dysregulation of Notch ligands, Jagged1 and Jagged2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…During MM progression, the so-called angiogenic shift occurs in the BMM, characterized by the increased capability of endothelial cells (ECs) to organize a network, migrate and express angiogenic factors fostering tumor cell proliferation. Palano et al reported that MM PCs-secreted Jagged 1 and 2 Notch ligands promoted angiogenesis in vitro as well as in a zebrafish MM model in vivo, thus representing novel targets to antagonize BM angiogenesis [3]. In parallel, Rao et al identified the HB-EGF-EGFR signaling pathway as relevant for MM angiogenesis, as shown by high levels of EGFR and HB-EGF in BM ECs from MM compared with monoclonal gammopathy of undetermined significance patients.…”
Section: Signals Arising From the MM Bone Marrow Microenvironment (Bmm)mentioning
confidence: 99%
“…During MM progression, the so-called angiogenic shift occurs in the BMM, characterized by the increased capability of endothelial cells (ECs) to organize a network, migrate and express angiogenic factors fostering tumor cell proliferation. Palano et al reported that MM PCs-secreted Jagged 1 and 2 Notch ligands promoted angiogenesis in vitro as well as in a zebrafish MM model in vivo, thus representing novel targets to antagonize BM angiogenesis [3]. In parallel, Rao et al identified the HB-EGF-EGFR signaling pathway as relevant for MM angiogenesis, as shown by high levels of EGFR and HB-EGF in BM ECs from MM compared with monoclonal gammopathy of undetermined significance patients.…”
Section: Signals Arising From the MM Bone Marrow Microenvironment (Bmm)mentioning
confidence: 99%
“…Angiogenesis is regulated by a broad spectrum of locally produced factors, with Vegf (A-E) members being main drivers of this process in MM [75] . Vegf factors bind to Vegf receptors 1-3, activate endothelial cells, and initiate angiogenesis [77] . The bone marrow microenvironment in MM also facilitates angiogenesis because it is extremely hypoxic, which stimulates the production and release of Vegf.…”
Section: Notch and Angiogenesismentioning
confidence: 99%
“…Endothelial cells from MM patients exhibit higher expression of Jagged 1 and 2, Notch receptors 1 and 2, and Notch target genes than endothelial cells from MGUS patients [78,79] . In vitro work has shown that Jagged-mediated signals from MM cells can increase angiogenesis by activating Notch and stimulating the release of Vegf in both endothelial cells and marrow stromal cells [77] . In vitro, genetic knockdown of Notch receptor 1/2 or blockade of Notch signaling with GSI decreased angiogenesis induced by MM cells.…”
Section: Notch and Angiogenesismentioning
confidence: 99%
“…NOTCH deregulation in MM cells is due to the aberrant expression of NOTCH receptors and/or ligands [15]. High levels of NOTCH pathway activity are associated with increased myeloma cell infiltration in BM biopsies of MM patients [16]. Other studies suggest that MM cell skeletal infiltration may be due to events promoted by NOTCH, including MM cell recruitment at the BM [17], mitogenic or anti-apoptotic effect [17][18][19], or MM stem cell self-renewal [20].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest that MM cell skeletal infiltration may be due to events promoted by NOTCH, including MM cell recruitment at the BM [17], mitogenic or anti-apoptotic effect [17][18][19], or MM stem cell self-renewal [20]. Additionally, MM infiltration of BM niche is also associated with the activation of NOTCH signaling in the tumor niche, which promotes angiogenesis [16,21], osteoclastogenesis [22][23][24], and bone marrow stromal cell (BMSC) release of cytokines involved in these events (IL-6, VEGF, IGF-1, SDF-1, RANKL, etc.) [16,18,19,25].…”
Section: Introductionmentioning
confidence: 99%